Dentistry Practice: Impact of COVID-19 Pandemic - Gupta, Sanjay Prasad (Europasian Journal of Medical Sciences, 2020)
Our world is under siege by a viral disease, named Corona virus disease 2019 (Covid-19). Corona virus (SARS-CoV-2) is transmitted directly from person to person by respiratory droplets through coughing, droplet inhalation transmission, sneezing, and indirectly through contact transmission with nasal, oral and eye mucous membranes contact. It is also transmitted to others by fecal–oral routes and saliva.1 In addition, it was confirmed that cases without symptoms can spread the virus.2-3 Why dentistry is a risk branch? The prime modes of containing this pandemic are enforcing effective social/physical distancing and use of masks but unfortunately it is not possible during carrying the dental procedures. Dental teams are at greater risk of infection as well as potentially transmit to others due to the nature of dentistry practice, specificity of its procedures, which involves face-to-face close contact, unable to worn masks by the patient during dental treatment, and frequent exposure to blood, saliva and other body fluids, and sharp instruments handling.